Diuretic Activity of the Hydroalcoholic Extracts of Rhizomes and Leaves of Artemisia Abyssinica Sch. Bip. ex A. Rich: In Silico and in Vivo Study - Abdu, Nebiyu; Alebachew, Yonatan (Scripta Medica, 2024)
Background/Aim: In addition to their adverse effects and drug-drug interactions, the affordability and availability of diuretics are a major problem in developing countries. Consequently, the majority of communities in developing nations utilise traditional medicine as an alternative or a combination therapy with a clinically approved diuretic regimen. The present study aimed to investigate the in vivo and in silico diuretic properties of the 80 % methanol extracts of the rhizomes and leaves of Artemisia abyssinica, an indigenous traditional diuretic medicinal plant of Ethiopia. Methods: Acute oral toxicity tests of 80 % methanol rhizome and leaf extracts of the plant were conducted in mice. For the diuretic test, six treatment groups were administered 100, 200 and 400 mg/kg doses of rhizome and leaf extracts of the plant. The negative and positive control groups were treated with distilled water (2 mL/100 g) and furosemide (10 mg/kg), respectively. Cumulative urine volume, diuretic action, diuretic activity and saluretic index were then determined. In addition, virtual screening and molecular docking study of the compounds of the genus Artemisia were done. Results: The rhizome and leaf extracts of A abyssinica were found safe at a dose of 2000 mg/kg. Moreover, both extracts showed a significant diuretic action (p < 0.05). However, compared to the standard drug furosemide, the extracts had lower diuretic activity. The rhizome extract increased electrolyte excretion at all doses; particularly at the 200 and 400 mg/kg doses, it exhibited a profound natriuretic, chloruretic and kaliuretic effect with the concentration of 109 and 110 mmol/L for Na+, 93 and 106 mmol/L for Cl‒ and 79 and 86 mmol/L for K+, respectively. These suggested inhibition of Na+-K+-2Cl‒ cotransporter as the potential mechanism of action of the extracts. Accordingly, virtual screening and a molecular docking analysis of the compounds of the genus Artemisia revealed that a few of them displayed a strong binding interaction with the cation-chloride cotransporter NKCC1 (PDB: 7S1Y), further indicating the cation-chloride cotransporter as a diuretic target of the constituents of the plant. Conclusion: The current study supports the traditional claim of the plant for diuresis and recommends further isolation of the active constituents.